Comparison of the Polymerization Shrinkage of Eclipse Resin for Prostheses with Conventional Acrylic Resins (2019)
: The objective of this study was to compare the polymerization shrinkage of Eclipse photopolymerization resin for prosthesis based on urethane dimethacrylate (UDMA) with that of three heat-cured acrylic resins based on polymethyl methacrylate (PMMA) af